Mengungkap Potensi Pertumbuhan Laba: Studi Kinerja Keuangan Di PT. PLN (Persero) UID Sulselrabar - Fadel Fadel; Faridah; Arif Mashuri; Nurhidayanti.S (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze financial performance in predicting profit growth at PT PLN (Persero) UID SULSELRABAR during the 2020-2022 period. The sample used consists of balance sheets and income statements from the financial reports of PT PLN. The method employed in this research is quantitative analysis, with a focus on profitability analysis. The results show that the company's financial performance, measured through the Profitability Ratio, particularly the Net Profit Margin, is considered suboptimal due to significant fluctuations over the study period. In 2021, Return on Assets (ROA) decreased by 16.62%, but it recovered with a 10% increase in 2022. Conversely, Return on Investment (ROI) showed significant improvement, rising from -43.92% in 2021 to -6.33% in 2022. However, Return on Equity (ROE) exhibited a negative trend, with a 20.75% decline in 2021, followed by a further decrease of 10.88% in 2022, indicating subpar performance. The company’s profit growth also experienced a drastic decline over the 2020-2022 period, with a 9.41% drop in 2022, reflecting challenges in maintaining profitability amidst fluctuating financial performance.